2018
DOI: 10.1038/s41598-018-35272-z
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of adenoid and tonsil growth in Japanese children and adolescents: A longitudinal study

Abstract: Lymphoid tissues, such as adenoids (Ad) and tonsils (Tn), are suggested to undergo hypertrophy during childhood and involution in adulthood. Enlargement of Ad and Tn can cause transient obstruction of the respiratory airways, thus inducing obstructive sleep apnoea. To date, the standard Ad and Tn sizes have not been reported, and there are no explicit objective criteria for evaluating their sizes or deducing whether they have enlarged, reduced, or remained constant over time. Our previous cross-sectional study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 33 publications
0
26
1
2
Order By: Relevance
“…Mental spine - clivus length and intermandibular length of children increase linearly with the age. Meanwhile, tonsils and adenoid grow proportionally to the skeletal structures at the same time 25 A longitudinal observational study showed that the tonsil and adenoid grow to maximum size at about ages of 7–9 and of 12–13, respectively 15,26 In this study, we included the children aged from 2 to 13 years old, who were the most common candidates for adenotonsillectomy. The results of the present study may be used to evaluate the surgical indications in children with OSA.…”
Section: Discussionmentioning
confidence: 99%
“…Mental spine - clivus length and intermandibular length of children increase linearly with the age. Meanwhile, tonsils and adenoid grow proportionally to the skeletal structures at the same time 25 A longitudinal observational study showed that the tonsil and adenoid grow to maximum size at about ages of 7–9 and of 12–13, respectively 15,26 In this study, we included the children aged from 2 to 13 years old, who were the most common candidates for adenotonsillectomy. The results of the present study may be used to evaluate the surgical indications in children with OSA.…”
Section: Discussionmentioning
confidence: 99%
“…Ishida et al [3] showed that the mean values of Ad and Ts were 347.55 ± 12.52 mm 2 and 161.34 ± 9.54 mm 2 in the younger primary school group and 346.22 ± 12.63 mm 2 and 152.82 ± 9.35 mm 2 in the older primary school group, respectively. Our results showed that the cross-sectional area of Ts was, on average, 125.91 mm 2 in the 2nd grade, 134.96 mm 2 in the 4th grade, and 135.56 mm 2 in the 6th grade.…”
Section: Discussionmentioning
confidence: 98%
“…All investigators were blinded to the general status of the participants. Figures 1 and 2 indicate the definitions of the points and lines used to identify the variables based on previous studies [1,3,9] and illustrate the linear and area measurements as the variables, respectively, as variables. Statistical analyses were performed using SPSS (version 22.0; SPSS Inc., Chicago, IL, USA) and the statistical package R (version 4.0.2; available as a free download from https: //www.r-project.org/, accessed on 25 September 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As adenoid is a lymphoid tissue, it is subjected to hypertrophy during childhood with subsequent involution in adulthood 2 . Recurrent upper respiratory tract infection may cause adenoiditis plus physiological hypertrophy that may lead to nasal obstruction, running nose, mouth breathing, snoring and obstructing sleep apnea 3 . Various methods are used in assessing the adenoid hypertrophy such as posterior rhinoscopic mirror examination, endoscopic assessment, and radiological investigations 4 .…”
Section: Introductionmentioning
confidence: 99%